Collecting evidence of FLEGT-VPA impacts: Global synthesis report - Cerutti, P.O.; Goetghebuer, T.; Leszczynska, N.; Newbery, J.; Almeida, B.; Tsanga, R.; Fourmy, R.; Ploeg, L. van der (Center for International Forestry Research, 2022)
This study synthesizes qualitative and quantitative evidence of EU-FLEGT Voluntary Partnership Agreement (VPA) impacts across seven countries – Cameroon, Ghana, Indonesia, Republic of Congo, Côte d’Ivoire, Guyana and Honduras. These countries are at different stages of the VPA process – from negotiation to implementation to issuance of Forest Law Enforcement, Governance and Trade (FLEGT) licences. By studying countries at different stages, findings allow for global lessons to be learned across different geographies and time.